New extensive focused AMS 14C dating of the Middle and Upper Magdalenian of the western Aquitaine/Pyrenean region of France (ca. 19–14 ka cal BP): Proposing a new model for its chronological phases and for the timing of occupation. (1st September 2016) - Barshay-Szmidt, Carolyn; Costamagno, Sandrine; Henry-Gambier, Dominique; Laroulandie, Véronique; Pétillon, Jean-Marc; Boudadi-Maligne, Myriam; Kuntz, Delphine; Langlais, Mathieu; Mallye, Jean-Baptiste
Abstract: In this paper we present all the AMS radiocarbon dates obtained for the 19 sites of the MAGDATIS project (69 results, including 4 human remains) and the approach we took to do this. This large-scale project involved a substantial multi-disciplinary re-assessment of the Middle and Upper Magdalenian of the western Aquitaine/Pyrenean region of France. Our principal questions in this project regarding this period and region related to the renewal (i.e. expansion and disappearance) of the ungulate community and the timing of major techno-economical innovations. Dating sites was a key aspect of this project. Many of these sites were excavated a long time ago, often without the benefit of taphonomic assessment at the time. As a result, careful selection of artifacts for dating was key to obtaining accurate and reliable results and thus our methodology is emphasized in this paper. Among specific results obtained through this project are that (1) based on a re-analysis of the techno-typology of the lithic and osseous industries, in conjunction with the new dates done, the Magdatis project is proposing a new finer subdivision of the Middle and Upper Magdalenian into 4 phases (early and late sub-phases in each) using Bayesian modelling to determine boundaries; (2) that the Middle Magdalenian began earlier than previously suspected (ca 18 800 vs 18 300 cal BP); (3) that there is a hiatus in occupation in the northern Aquitaine during the Late Middle Magdalenian whereas occupation is continuous closer to the Pyrenees. (4) We will also be presenting briefly in this paper the theory behind, approach to, and results of, the dating of Magdalenian human remains done in this project.